Strategi Post to Post untuk Meningkatkan Kemampuan Memecahkan Masalah Peserta Didik dalam Pembelajaran Pendidikan Pancasila - Gugum Gumilar; Anisa Ardiana; Meidha Zulva; M. Japar; Yuys Kardiman (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The learning model is one of the determinants of the achievement of learning objectives, post to post is a learning innovation that can be used by teachers to improve students' problem-solving abilities. Students' problem-solving abilities need to be developed today, considering the challenges of increasingly widespread developments, both science and technology. This study was conducted in class XI who were cognitively superior, but were still unable to respond to problems and provide solutions to solve problems. The purpose of this study was to find out students who had not been able to respond to problems and had not been able to find solutions, to find out the reasons why students had difficulty in developing strategies for solving problems. This study uses a descriptive qualitative approach study. The techniques used in this study were to collect data through observation, interviews, and documentation. The results of the study obtained showed that students using the post to post learning model can help in responding to problems, in addition, through post to post, students are given the opportunity to express their ideas, so that they become solutions that can be done when facing problems.